1984
DOI: 10.1159/000469455
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phosphofructokinase and Pyruvate Kinase in Rat Brain Regions during Alloxan-Induced Diabetes

Abstract: Changes in the profile of two glycolytic enzymes, phosphofructokinase and pyruvate kinase, in different regions of rat brain were studied under alloxan-induced diabetes. A regional variation of the effect of diabetes on brain was noted - the cerebral hemispheres and cerebellum showed decreased activity of the enzymes, while the brain stem remained relatively unaffected. The changes in enzyme activities in the brain regions were more pronounced at the early days of diabetes, particularly at 8 days. Insulin admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…[48] have also found that neonatal hypothyroidism decreases the flux of glucose into the glutamate, glutamine and GABA pools. In agreement with a depression of cerebral metabolism by hypothyroidism, phosphofructokinase and pyruvate kinase activities decrease in the cerebral hemispheres and cerebellum of hypothyroid rats [49].…”
Section: Discussionsupporting
confidence: 65%
“…[48] have also found that neonatal hypothyroidism decreases the flux of glucose into the glutamate, glutamine and GABA pools. In agreement with a depression of cerebral metabolism by hypothyroidism, phosphofructokinase and pyruvate kinase activities decrease in the cerebral hemispheres and cerebellum of hypothyroid rats [49].…”
Section: Discussionsupporting
confidence: 65%
“…Although phosphofructokinase was found in both types of brains, it has been reported that the levels of this enzyme are decreased in diabetic brains [27]. A number of cytoplasmic proteins were also identified in both the non-diabetic and diabetic brains: glycolipid transfer protein, a protein that accelerates the intermembrane transfer of various glycolipids [28]; ubiquitin protein ligase E3C, which is thought to be the component of the ubiquitin conjugation system most directly responsible for substrate recognition [29,30] and modulating the function of the synapse [31]; and heat shock protein 8 (HSP70).…”
Section: Resultsmentioning
confidence: 90%
“…It appears, therefore, that the observed decrease in the activity of Ala-AT in cerebral hemispheres could be due to a decreased glycolytic flux during diabetes. To this effect, the key glycolytic enzymes, name ly, phosphofructokinase and pyruvate kinase, have also been shown to decrease in cerebral hemispheres and cerebellum with no signifi cant change in brain stem [16].…”
Section: Resultsmentioning
confidence: 99%